Predictors of Cardiovascular Autonomic Neuropathy in Patients with Type 1 Diabetes - Tannus, Lucianne Righeti Monteiro; Drummond, Karla Rezende Guerra; Clemente, Eliete Leão da Silva; da Matta, Maria de Fátima Bevilacqua; Gomes, Marilia Brito; , on behalf of the Brazilian Type 1 Diabetes Study Group (BrazDiab1SG) (Frontiers in Endocrinology, 2014)
Cardiovascular disease (CVD) is the leading cause of mortality in patients with type 1 diabetes (T1D). The cardiovascular autonomic neuropathy (CAN), although considered as an independent risk factor for CVD, remains underdiagnosed. The aim of this paper was to determine the prevalence, predictors of CAN in patients with T1D and its association with other chronic complications of diabetes. Patients with T1D underwent a clinical-epidemiological survey, had blood and urinary samples collected, performed ophthalmoscopic and clinical neurological examination and cardiovascular reflex tests. One hundred and fifty one patients with T1D, 53.6 % female, 45.7% caucasian, mean age of 33.4 ± 13 years, diabetes duration of 16.3 ± 9.5 years, glycated hemoglobin levels of 9.1 ± 2% were evaluated. The prevalence of CAN in the studied population was 30.5%. CAN was associated with age (p=0.01), diabetes duration (p=0.036), hypertension (p=0.001), resting heart rate (p=0.000), HbA1c (p=0.048), urea (p=0.000), creatinine (p=0.008), glomerular filtration rate (p=0.000), urinary albumin concentration (p=0.000), LDL (p=0.048), free T4 (p=0.023), hemoglobin (p=0.01) and presence of retinopathy (p=0.000), nephropathy (p=0.000) and diabetic neuropathy (p=0.000), the following symptoms syncope (p=0.000), post prandial nausea (p=0.042), early satiety (p=0.031), sexual dysfunction (p=0.049) and gustatory sweating (p=0.018). In logistic regression model, it was observed that only age, resting heart rate, diabetic nephropathy and retinopathy were independent associated with CAN. In conclusion, CAN is a common chronic complication of T1D affecting about 30% of the studied population and is associated with the presence of other chronic complications. Indicators of CAN included age, diabetes duration, hypertension, resting heart rate, diabetic nephropathy and retinopathy and symptoms suggestive of autonomic neuropathy. This study confirms the importance of systematic and early screening for CAN.